Plasmodesmata and intercellular transport of viral RNA. (22nd January 2007) - Hofmann, C.; Sambade, A.; Heinlein, M.
Abstract : Cell-to-cell communication in plants involves the symplastic trafficking of informational protein and RNA macromolecules through cytoplasmic bridges in the plant cell wall known as plasmodesmata. Viruses exploit this route for the spread of infection and are used as a model to study the mechanisms by which macromolecules are targeted to the pore. Studies using tobacco mosaic virus have led to the identification of host components that participate in plasmodesmal targeting of viral RNA and movement protein.